2019
DOI: 10.1111/1754-9485.12971
|View full text |Cite
|
Sign up to set email alerts
|

Survival, tumour response and safety of 70‐150 μm versus 100‐300 μm doxorubicin drug‐eluting beads in transarterial chemoembolisation for hepatocellular carcinoma

Abstract: Introduction This study investigates the outcomes and safety of 70–150 μm and 100–300 μm doxorubicin drug‐eluting bead transarterial chemoembolisation (DEB‐TACE) in patients with unresectable hepatocellular carcinoma (HCC). Methods Retrospective, cohort study of 51 patients treated with DEB‐TACE for unresectable HCC was studied: 23 with 100–300 μm particles and 28 with 70–150 μm particles. Overall, survival (OS), progression‐free survival (PFS), tumour response and prognostic factors were assessed. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…Recent studies have shown that patients with HCC receiving smaller microspheres showed better tumor response, better survival outcomes, fewer adverse events, and fewer patient complications [ 32 , 33 ]. However, using microspheres that are too small may lead to worse results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that patients with HCC receiving smaller microspheres showed better tumor response, better survival outcomes, fewer adverse events, and fewer patient complications [ 32 , 33 ]. However, using microspheres that are too small may lead to worse results.…”
Section: Discussionmentioning
confidence: 99%
“…This theory was supported by a recent study in patients with liver malignancies in whom DEBs with small diameters achieved improved the radiological response in terms of extensive intratumoral necrosis 12 . DEB-TACE with 70-150 µm particles demonstrated an improved 1-month objective tumor response compared to that with 100-300 µm particles in patients with HCC, while having a similar safety profile 13 .…”
mentioning
confidence: 86%
“…Transcatheter arterial chemoembolization (TACE) is currently used as a first‐line therapy for BCLC B stage unresectable HCC. [ 97–99 ] In fact, TACE is the loco‐regional treatment to selectively block tumoral blood supply partially or more completely. [ 100 ] Using a microcatheter, chemotherapeutics with the drug encapsulated are infused followed by the embolic agent clinically, which provides theoretical support for improving the efficiency of perfusion chemotherapy with nanotechnology.…”
Section: Therapeutic Advances For Hcc Managementmentioning
confidence: 99%